COVID-19 in pregnant women: a comparative observational study of pregnancy outcome in three waves of COVID-19 in district hospital, Ballari - Joshi, Suyajna D.; G., Vijayalakshmi; Banu, Ruksar; G., Jayasakthi; A., Shrilakshmi R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: A three wave pattern of corona virus has been seen in many countries during the 2020 pandemic. Observed data show that the effects of the virus do vary between the three waves. Differences in severity of the disease have been reported, although the comparative characteristics of the three waves still remain largely unknown. Methods: This was a prospective cross sectional study continuation of our first paper comparing 133 pregnant COVID- 19 positive patients in the first wave and 251 patients admitted during second wave and 92 patients in third wave who delivered at district hospital, Bellary. Results: In the present study 72.8% patients were in the age of 20-30 years, 85.87% patients belong to lower socio- economic status, mild anaemia about 32.6% in third wave, moderate anaemia seen in 10.8% in third wave, and 3.44% had severe anaemia. Non-severe pre-eclampsia was present in 10.8% of the patients, severe pre-eclampsia was seen in 6.52% of the cases and. Mode of delivery was 29.34% FTND, 3.26% FTVD emergency LSCS was 63.06% in third wave, and preterm delivery was seen in 4.34% in third wave. Elevated levels of D-dimer were found 25% in third wave. 0 deaths being reported in third wave. Conclusions: This study compared the obstetric and clinical outcome in COVID-19 positive patients who are in labor in first, second, and third wave of COVID-19 infection. Although our conclusions are limited, the finding so obtained are important for understanding the clinical parameters, obstetric parameters and perinatal outcome in three waves.